Introducción al pensamiento filosófico de Sócrates, Platón y Aristóteles. Cartilla virtual para estudiantes de educación media que inician estudios de filosofía. (2021)
This document justifies the conception of the virtual primer entitled: Introduction to the philosophical thought of Socrates, Platon and Aristotle. In the present document we will explain some of the most important issues raised by the philosophers mentioned before; the implementation of this material is thought as an introduction to the study of philosophy, for tenth grade students from public schools in Bogotá